Good manufacturing practice inspections conducted by Tanzania medicines and medical devices authority: a comparative study of two fiscal years from 2018 to 2020 - Raphael Zozimus Sangeda; Chimpaye Julius Ndabatinya; Maganga Bundala Maganga; Emmanuel Alphonce Nkiligi; Yonah Hebron Mwalwisi; Adam Mitangu Fimbo (Taylor & Francis Group, 2024)
Background Good Manufacturing Practices (GMP) is the bedrock of quality assurance in the pharmaceutical industry that ensures that products are consistently produced and controlled according to quality standards. This study compared the GMP conformance of pharmaceutical facilities across two fiscal years, 2018/2019 and 2019/2020, using the East African GMP Compendium on Good Manufacturing Practices, 2014, as a benchmark.Methods We analyzed the proportion of conformance of foreign pharmaceutical industries to GMP standards and reported the aggregated data over a two-year period.Results Inspected facilities had notable non-conformances, most commonly related to laboratory quality control and premises. We noted a downward trend in conformance in 2019/2020 compared with 2018/2019, with only 32.9% of facilities adhering to EAC GMP requirements, down from 50% in the previous year. The COVID-19 pandemic has affected the ability to conduct on-site inspections, and may have contributed to the lower conformance rate.Conclusions These findings underscore the crucial need to continue GMP inspections and the importance of taking corrective actions to ensure adherence to the quality standards for products marketed in Tanzania. The study further revealed the significance of desk reviews in assisting regulatory authorities in facing unforeseen challenges such as pandemics.